Developing an initial inventory of non-native invasive species based on roadside surveys: recent experience in southern and eastern Africa - Witt, Arne; van Wilgen, Brian; Beale, Tim (African Biodiversity & Conservation, 2026)
Background: Lists of non-native invasive species are needed for the development of strategies and plans to control them.Objectives: This paper describes the development of an initial inventory of non-native plants based on roadside surveys, and reviews the advantages and challenges associated with the methodology.Methods: We conducted surveys in 11 southern and eastern African countries and listed the presence of non-native plants at just under 107 000 roadside localities between 2008 and 2019. Localities were georeferenced and used to create a database of the distribution of 708 non-native plant species.Results: The survey effort varied between countries, with sampling taking place fairly comprehensively in smaller countries (e.g., Eswatini, Malawi and Rwanda were well covered, with >90% of half-degree grid cells reached), while coverage was acceptably high in Uganda, Kenya and Tanzania (78–49%). In other countries, coverage was less. The greatest number of non-native species was recorded in Kenya (430), followed by Tanzania (341), Malawi (313) and Zambia (240). The most frequently recorded species was Lantana camara, with 5 566 records, followed by Senna siamea (3 526), Eucalyptus spp. (3 409), Ricinus communis (3 261) and Cascabela thevetia (3 156). Our inventories made a significant contribution to the regional database, constituting 58% of all plant observations in GBIF across the 11 countries in 2018. Several field guides have been produced based on these lists, and they provide a useful resource where none existed until recently.Conclusion: Alternative methods exist for the development of lists, including remote sensing and citizen science, and each has advantages and drawbacks. Roadside surveys are not comprehensive as they are limited to roadsides and subject to several potential biases because inconspicuous species are excluded, and observers have different levels of competence. We conclude nonetheless that roadside surveys, undertaken by experienced observers during the course of other duties that involve widespread travel, can provide a relatively inexpensive and very useful initial inventory, especially in lower- and middle-income countries where the capacity to conduct other survey options is lacking.